2019
DOI: 10.15517/rbt.v67i1.33168
|View full text |Cite
|
Sign up to set email alerts
|

Estratificación vertical de arañas tejedoras (Araneae) en fragmentos de bosque seco tropical del Caribe colombiano

Abstract: Las arañas han logrado colonizar la mayoría de ambientes terrestres, siendo comunes en los bosques. Este grupo se ha reportado desde el suelo hasta el dosel y sus patrones de distribución vertical han demostrado ser variables en distintos ecosistemas. Teniendo en cuenta esta variabilidad, el objetivo de este trabajo fue analizar los cambios en composición y diversidad de arañas tejedoras en un plano vertical en dos fragmentos de bosque seco con diferente calidad estructural de la vegetación. Para ello fueron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…In a spatially randomly or homogeneously distributed habitat (i.e., trees without epiphyte aggregations), spider patches occur, and are probably the result of processes that operate after the colonization of a site (sensu Sereda et al, 2012). For example, Hodge Cuervo et al, 2019;Vanegas et al, 2012). These gradients have been attributed to different factors dependent on the type of ecosystem (Pinzon et al, 2013), such as environmental filters (Oguri et al, 2014;Quijano-Cuervo et al, 2019), variation in the structural complexity between vegetation strata (Oguri et al, 2014), and biotic interactions like competition (Basset et al, 2003;Brown, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a spatially randomly or homogeneously distributed habitat (i.e., trees without epiphyte aggregations), spider patches occur, and are probably the result of processes that operate after the colonization of a site (sensu Sereda et al, 2012). For example, Hodge Cuervo et al, 2019;Vanegas et al, 2012). These gradients have been attributed to different factors dependent on the type of ecosystem (Pinzon et al, 2013), such as environmental filters (Oguri et al, 2014;Quijano-Cuervo et al, 2019), variation in the structural complexity between vegetation strata (Oguri et al, 2014), and biotic interactions like competition (Basset et al, 2003;Brown, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported vertical gradients for the abundance, richness, and composition of arboreal spider communities (Méndez‐Castro & Rao, 2014; Pinzon et al, 2011; Quijano‐Cuervo et al, 2019; Vanegas et al, 2012). These gradients have been attributed to different factors dependent on the type of ecosystem (Pinzon et al, 2013), such as environmental filters (Oguri et al, 2014; Quijano‐Cuervo et al, 2019), variation in the structural complexity between vegetation strata (Oguri et al, 2014), and biotic interactions like competition (Basset et al, 2003; Brown, 1981). For our scenario, the decreasing gradients (from the ground to the canopy) in richness and abundance of epiphytes and spiders are possibly associated with gradients of increasing temperature and decreasing humidity that occur between the vertical layers of tropical forest ecosystems (Freiberg, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this method, spiders, at the species or family level, have been assessed as indicators of different groups. For example, habitat (Ghione et al 2013;Aisen et al 2017;Quijano-Cuervo et al 2019), habitat in a gradient of disturbance (Kaltsas et al 2014;Argañaraz et al 2020a; van Rensburg et al 2020), management (Torma et al 2019;Argañaraz et al 2020b;Topa et al 2021), succession and restoration (Cristofoli et al 2010;Malumbres-Olarte et al 2013;Yekwayo et al 2019), pollution (Horváth et al 2001;Nahmani et al 2006), soil quality (Nuria et al 2011;Rousseau et al 2013), colonization of agroecosystems (Royauté and Buddle 2012), forest fragmentation and degradation (do Amaral Nogueira and Pintoda-Rocha 2016), seasons (Campuzano and Padilla-Ramírez 2021) and ecosystem services (Elie et al 2018). However, the majority of the research mentioned was carried out in non-South American countries.…”
Section: ₁₁₂₁ I�����������mentioning
confidence: 99%
“…Ecología Austral 32:1120-1132 Quijano-Cuervo et al (2019) and Yekwayo et al (2019) were the only ones to evaluate plantdwellers spiders as bioindicators collecting spiders from the foliage of trees and grasses, respectively.…”
Section: ₁₁₂₂ Mf N����mentioning
confidence: 99%